Transformational Leadership and Management of the Organization Sufficiency Economy Philosophy with The Operation of Small Enterprises in Nakhonratchasima - บัดทิม, เกศรินทร์ (RMUTI Journal Humanities and Social Sciences, 2015)
The purpose of this research was to study transformational leadership and management of the organization sufficiency economy philosophy with operation of small enterprises in Nakhonratchasima. The samples used were 382 persons core sampling using probability sampling methods precedent and simple. Statistics used to analyze the data were mean, percentage, frequency, standard deviation (S.D.) and multiple regression analysis. The result of transformational leadership found idealized influence, inspiration motivational, intellectual stimulation and individual consideration, the overall mean at the highest level. Management of the organization sufficiency economy philosophy found moderation, reasonableness, self-immunity, set of knowledge and ethical qualification, the overall mean at the highest level, and the operation of small enterprises in Nakhonratchasima found customer, internal process, learning and growth and financial. The overall mean at the highest level. For hypothesis testing found transformational leadership and management of the organization sufficiency economy philosophy. The affect on the operation of small enterprises in Nakhonratchasima, was that income and sales increased. The associated costs are reasonable. Customer satisfaction with regard to products and services rose by a statistically significant level of 0.05. Future product for customer satisfaction increases could be as high as 75.50 percent.